(untitled) (Journal of Asian Development Studies, 2024)
This study analyses the opportunities and impact of women’s political participation in Khyber Pakhtunkhwa (KP), Pakistan, focusing on unlocking the potential for greater inclusivity and socio-political advancement. This research examines the barriers and opportunities influencing female political engagement in a region characterized by its unique socio-cultural dynamics and historical marginalization of women. The study identifies critical impediments such as socio-cultural norms, lack of educational opportunities, and limited access to resources by employing a mixed-methods approach, including qualitative interviews and quantitative surveys. Simultaneously, it highlights emerging opportunities for women in politics, including legislative reforms, grassroots movements, and increased support from civil society organizations. The impact of women’s participation in governance, policy-making, and community development is analyzed to understand how increased female representation can contribute to more equitable and effective political systems. The findings underscore the potential benefits of enhancing women’s political engagement, including improved policy outcomes and greater social cohesion. This research aims to provide actionable insights for policymakers, activists, and scholars seeking to foster an inclusive political environment in KP and beyond.